Severe secondary hyperparathyroidism in a chronic kidney disease patient treated with Radiofrequency ablation: One case report - Muhetaer, Gulimire; Liu, Guangyi; Zhang, Ling; Jiang, Hong (Frontiers in Medicine, 2022)
Abstract End-stage renal disease (ESRD) is a global health problem with a high incidence [1] and a steadily increasing prevalence [2]. Secondary hyperparathyroidism (SHPT) is a common and serious complication of chronic renal failure (CRF) in dialysis patients [3]. It is mainly manifested as parathyroid hyperplasia caused by abnormal calcium and phosphorus metabolism and active vitamin D resistance, resulting in excessive secretion of parathyroid hormone (PTH), which leads to complications such as bone deformity, osteoarthralgia, pruritus, ectopic calcification, and cardiovascular calcification in CKD patients, significantly reducing the quality of life in CKD patients[4, 5]. In patients with chronic kidney disease, secondary parathyroid gland hyperplasia needs to be treated as early as possible [6]. Currently, there are a variety of treatment options, including vitamin D receptor agonists, xenacax hydrochloride, parathyroidectomy and ablation techniques, etc. [7, 8]. Medical treatment is the main choice among these treatments, but it is invalid in patients with severe hyperparathyroidism. So, parathyroidectomy is suggested to do in those patients. [9].However, many dialysis patients who have severe cardiopulmonary dysfunction cannot tolerate the trauma caused by surgery as the concept of minimally invasive surgery has been gradually introduced into all fields of surgery and medical treatment. Traditional surgery is no longer the only option. Radiofrequency ablation has been widely applied due to its advantages of less trauma, simple operation, and good repeatability. It has been reported to achieve good effects in treating secondary hyperparathyroidism patients [8]. This case reports that one severe secondary hyperparathyroidism patient gets good therapeutic results from parathyroid radiofrequency ablation.